Implementing the rasch model to assess the level of students' critical and reflective thinking skills on the photoelectric effect - Tarpin Juandi; Ida Kaniawati; Achmad Samsudin; Lala Septem Riza (Universitas PGRI Kanjuruhan Malang, 2023)
This study aims to determine the level of studentsâ€™ critical and reflective thinking skills on the topic of photoelectric effects. In this study, the cross-sectional survey approach was employed in conjunction with purposive sampling techniques.Â The data collection instruments are questionnaires for critical thinking and reflective thinking skills, with 20 critical thinking items and 24 reflective thinking items. A total of 35 students, 6 males and 29 females, with an average age of 20 years, agreed to fill out the questionnaire that was distributed. The acquired quantitative data were evaluated using the Rasch model, with critical thinking skills showing that 11% of students were at a very low level, 49% were at a low level, 26% were at a high level, and 14% were at a very high level. Meanwhile, data analysis of reflective thinking skills revealed that 20% of pupils had low levels, 63% had moderate levels, and 17% had high levels. As a result, it is suggested that critical thinking and reflective thinking skills be continuously debriefed.